Revolutionizing Hospitality: Unraveling the Transformative Potential of Big Data in Tourism and Hotel Management - Lin Mu; Qianzi Guo; Lin Yang (HighTech and Innovation Journal)
Objective: The purpose of this research is to investigate how big data analysis may be used in the tourist and hotel sectors to improve customer happiness and spur corporate expansion. The goals are to analyze traveler behavior and preferences, derive actionable insights from a variety of data sources, and design customized strategies to enhance customer experiences and promote brand loyalty. Methods/Analysis: To ensure precision and comprehensiveness, the approach incorporates rigorous preprocessing procedures for data. This technique is essential for providing precise insights into the customers, both explicit and implicit. The study provides a thorough understanding of consumer interactions and preferences by including data from social media, travel websites, and hotel booking systems. Findings: The research offers significant insights that demonstrate the capacity to improve consumer experiences, tailored products, optimized services, and effective marketing tactics. The results emphasize how important it is to understand client preferences to inform corporate strategy and create a competitive edge. Conclusion: The potential of big data analysis in the travel and hospitality sectors is shown in this research, which adds to the rapidly developing subject. This study highlights how big data analysis plays a critical role in enhancing the tourist experience and promoting industry innovation by clarifying the relationship between technology and customized services.